2016
DOI: 10.1177/0002716215625038
|View full text |Cite
|
Sign up to set email alerts
|

“A Twenty-Hour-a-Day Job”

Abstract: In the growing field of research on the consequences of criminal justice contact for family life, a heavy emphasis has been placed on how imprisonment influences the emotional, physical, and socioeconomic wellbeing of prisoners’ loved ones. In this article, I elaborate on and analyze the experiences of family members of people with frequent, low-level criminal justice involvement. I draw on ethnographic data collected in partnership with a clinical social worker over the course of a three-year study of an inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(43 citation statements)
references
References 41 publications
2
37
0
Order By: Relevance
“…Men's repeated cycles of incarceration and reentry may contribute to mothers' efforts to protect children from disappointment, hold fathers at a distance, and lessen or halt women's prison work. Frequent cycles of incarceration and reentry can be uniquely destabilizing for families, deplete emotional and financial resources for caregivers, and stress children (Comfort, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Men's repeated cycles of incarceration and reentry may contribute to mothers' efforts to protect children from disappointment, hold fathers at a distance, and lessen or halt women's prison work. Frequent cycles of incarceration and reentry can be uniquely destabilizing for families, deplete emotional and financial resources for caregivers, and stress children (Comfort, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Although there was no average direct effect of CFI, HI, or PI on social support, such average effects may obscure positive or negative effects on certain subgroups within this population. The strong emotional responses to family imprisonment observed in qualitative research with prisoners' relatives in Australia as well as other countries (e.g., Braman, 2004;Comfort, 2008Comfort, , 2016Condry, 2013;Dennison & Besemer, in press;Meek, 2008) may be indicative of such subgroup effects. It is possible that such studies capture families affected by longer and more serious prison sentences, and therefore, finds much greater negative psychological consequences in family members affected.…”
Section: Discussionmentioning
confidence: 99%
“…Although many qualitative studies suggest that imprisonment diminishes the psychological well-being of prisoners' family members and spouses (e.g., Braman, 2004;Comfort, 2008Comfort, , 2016Condry, 2013;Dennison & Besemer, in press;Meek, 2008), few studies have tested this effect empirically. A number of cross-sectional studies have shown that family imprisonment is associated with substantially worse physical and mental health (K. L. Besemer & Dennison, in press;Gaston, 2016;Wildeman, Lee, & Comfort, 2013).…”
Section: Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Jail stays also interrupt employment which can negatively earnings (Harding, Siegel, & Morenoff, 2017). The strain of jail can make it difficult to maintain relationships that are essential to successful reintegration back into society (Apel, 2016;Comfort, 2016). The churn of multiple jail stays, even if short in length, also causes strain and instability among family groups, leaving families feeling hopeless under the constant eye of supervision (Comfort, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%